The use of a contextual, modal and psychological classification of medication errors in the emergency department: a retrospective descriptive study. Issue 23 (27th March 2017) - Cabilan, CJ; Hughes, James A; Shannon, Carl
Abstract : Aims and objectives: To describe the contextual, modal and psychological classification of medication errors in the emergency department to know the factors associated with the reported medication errors. Background: The causes of medication errors are unique in every clinical setting; hence, error minimisation strategies are not always effective. For this reason, it is fundamental to understand the causes specific to the emergency department so that targeted strategies can be implemented. Design: Retrospective analysis of reported medication errors in the emergency department. Methods: All voluntarily staff‐reported medication‐related incidents from 2010–2015 from the hospital's electronic incident management system were retrieved for analysis. Contextual classification involved the time, place and the type of medications involved. Modal classification pertained to the stage and issue (e.g. wrong medication, wrong patient). Psychological classification categorised the errors in planning (knowledge‐based and rule‐based errors) and skill (slips and lapses). Results: There were 405 errors reported. Most errors occurred in the acute care area, short‐stay unit and resuscitation area, during the busiest shifts (0800–1559, 1600–2259). Half of the errors involved high‐alert medications. Many of the errors occurred during administration (62·7%), prescribing (28·6%) and commonly during both stages (18·5%). Wrong dose, wrong medication and omission were the issues that dominated. Knowledge‐based errors characterised the errors that occurred in prescribing and administration. The highest proportion of slips (79·5%) and lapses (76·1%) occurred during medication administration. It is likely that some of the errors occurred due to the lack of adherence to safety protocols. Conclusion: Technology such as computerised prescribing, barcode medication administration and reminder systems could potentially decrease the medication errors in the emergency department. There was a possibility that some of the errors could be prevented if safety protocols were adhered to, which highlights the need to also address clinicians' attitudes towards safety. Relevance to clinical practice: Technology can be implemented to help minimise errors in the ED, but this must be coupled with efforts to enhance the culture of safety.